Comprehensive Characterization of Multi-Phase Sulfurized Polyacrylonitrile Cathodes for Lithium-Sulfur Batteries. Issue 7 (1st July 2022) - Langrud, Strauss; Razzaq, Amir Abdul; Santhanagopalan, Shriram; Brow, Ryan; Xing, Weibing
Abstract : Sulfurized polyacrylonitrile (SPAN) is considered one of the most promising cathode materials to overcome the operational challenges that plague lithium-sulfur (Li-S) batteries. However, material properties and electrochemical performance implications of SPAN prepared under different synthesis conditions are not yet fully investigated. In this study, we show the impacts of different synthesis conditions on the formation of sulfur to PAN bonds and redox reaction mechanisms of multi-phase SPAN via comprehensive material and electrochemical characterizations. In-situ Raman analysis was first applied to study the multi-phase SPAN-based Li-S cells. We found that both elemental sulfur and chemically bonded sulfur are present under the synthesis condition of 300 °C/3 h along with unreacted PAN. The incompletely sulfurized, multi-phase SPAN exhibited an unusually rapid capacity degradation in the resultant Li-S cells, which is attributed to polysulfide formation and continuously growing interfacial impedance in the Li-S cells. On the other hand, SPAN samples prepared under the synthesis condition of 350 °C/3 h are found completely sulfurized with chemically bonded sulfur to the PAN backbone without the presence of free elemental sulfur. Complete sulfurization of SPAN led to exceptionally stable cycle performance due to excellent reversible redox processes of chemically bonded sulfur with Li + in the Li-S cells.